2012
DOI: 10.1111/j.1742-1241.2011.02888.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual-centre, cohort comparison of open, laparoscopic and robotic-assisted radical cystectomy

Abstract: Despite study limitations, RARC had the lowest transfusion and complication rates and the shortest length of stay, although taking the longest to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 31 publications
8
79
1
1
Order By: Relevance
“…3). In two comparative nonrandomized studies between RARC and LRC, no significant differences in PSM rates were detected (p = 0.86) [87,89]. PLND, in conjunction with radical cystectomy, provides a staging benefit as well as a possible advantage for survival in retrospective studies.…”
Section: Potency Recovery After Robot-assisted Radical Cystectomymentioning
confidence: 99%
See 2 more Smart Citations
“…3). In two comparative nonrandomized studies between RARC and LRC, no significant differences in PSM rates were detected (p = 0.86) [87,89]. PLND, in conjunction with radical cystectomy, provides a staging benefit as well as a possible advantage for survival in retrospective studies.…”
Section: Potency Recovery After Robot-assisted Radical Cystectomymentioning
confidence: 99%
“…Exceptions included prospective studies [8,22,28,35,36,43,52,59,64,66,81,87] and some multi-institutional retrospective collaboration studies [16,23,25,30,45,48,54,61,68]. Only two of the comparative studies were randomized [74,83] (LOE 2b); all other comparative studies were nonrandomized, whether prospective or retrospective (LOE 4).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on early experience, we estimated the RARC complication rate as 10-15% [15] and that for ORC as 25-60% [16]. Therefore, the number needed in each arm ranges from 43 to 58 so the 95% confidence interval (CI) for the estimated difference in rates is AE16%.…”
Section: Power Calculations and Statistical Analysismentioning
confidence: 99%
“…A single small randomized trial [34] and the majority of retrospective and prospective matched case-control studies have reported no difference in lymph node yield between open, laparoscopic, and/or robotic cystectomy [35][36][37], although some groups have reported higher nodal yield with the robotic approach [38 & ]. Comparative analysis of oncologic outcomes between open and minimally invasive cystectomy is confounded by selection bias as the majority of minimally invasive series had a small proportion of patients with nonorgan-confined disease and nodal metastases [39,40].…”
Section: Bladder Cancermentioning
confidence: 99%